Reunión con Rodrigo Arias. (UNED, 2025)
Grupo mediano de personas, aparecen Rodrigo Arias, Roberto Román, Annie Umaña, Miguel Gutiérrez, Maricruz Corrales, Carlos Morgan, Jorge Múnera, Gustavo Amador, Patricia Quesada